Estimation of energy balance and training volume during Army Initial Entry Training. Issue 1 (28th November 2018) - McAdam, Jeremy; McGinnis, Kaitlin; Ory, Rian; Young, Kaelin; Frugé, Andrew D.; Roberts, Michael; Sefton, JoEllen
Abstract: Background: Adequate dietary intake is important for promoting adaptation and prevention of musculoskeletal injury in response to large volumes of physical training such as Army Initial Entry Training (IET). The purpose of this study was to evaluate training volume and dietary intake and estimate energy balance in Army IET soldiers. Methods: Dietary intake was assessed by collecting diet logs for three meals on each of three, non-consecutive days during the first week of IET. Training volume was measured across 13 weeks of training using Actigraph wGT3X accelerometers. Training intensity was classified using Sasaki vector magnitude three cut points. Energy expenditure estimates were calculated during weeks two and three of training using the modified Harris-Benedict equation and by estimation of active energy expenditure using metabolic equivalents for each classification of physical activity. All data is presented as mean ± standard deviation. Results: A total of 111 male soldiers (ht. = ± 173 ± 5.8 cm, age = 19 ± 2 years, mass = 71.6. ± 12.4 kg) completed diet logs and were monitored with Actigraphs. IET soldiers performed on average 273 ± 62 min low, 107 ± 42 min moderate, 26 ± 22 min vigorous, and 10 ± 21 min of very vigorous intensity physical activity daily across 13 weeks. The estimated total daily energy expenditure was on average 3238 ± 457 kcals/d during weeks two and three of IET. Compared to week one caloric intake, there was a caloric deficit of 595 ± 896 kcals/d on average during weeks two and three of IET. Regression analysis showed that body weight was a significant predictor for negative energy balance (adj. R2 = 0.54, p < 0.001), whereby a 1 kg increase in body mass was associated with a 53 kcal energy deficit. Conclusions: Based on week one dietary assessment, IET soldiers did not consume adequate calories and nutrients to meet training needs during red phase (weeks one through three). This may directly affect soldier performance and injury frequency. IET soldiers undergo rigorous training, and these data may help direct future guidelines for adequate nourishment to optimize soldier health and performance.